Perceptions dynamics about antiretroviral treatment among HIV patients in Bali - Anak Agung Sagung Sawitri; I Nyoman Sutarsa; Tuti Parwati Merati; Made Bakta; Dewa Nyoman Wirawan (Intelektual Pustaka Media Utama, 2021)
Perceptions of people living with HIV and AIDS (PLHIV) about antiretroviral treatment (ART) is crucial for improving adherence. This study aims to examine the dynamics of perceptions during the early phase of ART. A longitudinal study involving newly diagnosed PLHIV was conducted. Interviews were carried out at the time of HIV diagnosis and at three months after ART initiation. Data were analyzed by comparing proportion of good perception across the continuum of HIV diagnosis, ART initiation and threemonths follow-up, and were tested using Chi-square. From 170 PLHIV participated in the study, 81.76% had initiated ART and 73.4% remained on ART at three-months of follow-up. Several positive perception items were significantly decreased: ability to take ART at work and ability to continue treatment if experiencing side effects, effectiveness of ART, confidentiality, unwanted disclosure, and level of support from outreach workers. Ability to follow instruction from physician was significantly increased, and negative attitudes toward ART were decreased across the continuum. Adherence to ART is a continuous process, and is influenced by the dynamics perceptions among PLHIV. Understanding these dynamics is crucial to formulate strategies that can promote and maintain positive attitudes toward ART as well as living with HIV more broadly.